Redox-Induced Hydrogen Bond Reorientation Mimicking Electronic Coupling in Mixed-Valent Diruthenium and Macrocyclic Tetraruthenium Complexes - Fink, Daniel; Staiger, Anne; Orth, Nicole; Linseis, Michael; Ivanovic-Burmazovic, Ivana; Winter, Rainer F. (Inorganic Chemistry, 2020)
We present the coordination-driven self-assembly of three tetranuclear metallacycles containing intracyclic NH2, OH, or OMe functionalities through the combination of various isophthalic acid building blocks with a divinylphenylene diruthenium complex. All new complexes of this study were characterized by means of nuclear magnetic resonance spectroscopy, ultrahigh-resolution ESI mass spectrometry, cyclic and square wave voltammetry and, in two cases, X-ray diffraction. The hydroxy functionalized macrocycle 4-BOH and the corresponding half-cycle 2-OH stand out, as their intracyclic OH···O hydrogen bonds stabilize their mixed-valent one- (2-OH, 4-BOH) and three-electron-oxidized states (4-BOH). Despite sizable redox splittings between all one-electron waves, the mixed-valent monocations and trications do not exhibit any intervalence charge-transfer band, assignable to through-bond electronic coupling, but nevertheless display distinct IR band shifts of their charge-sensitive Ru(CO) tags. We ascribe these seemingly contradicting observations to a redox-induced shuffling of the OH···O hydrogen bond(s) to the remaining, more electron-rich, reduced redox site.
CRIS-Team Scopus Importer:2020-11-27